Behavior therapy for a 75-year-old woman with chronic motor tic disorder. (October 2013) - McGuire, Joseph F; Storch, Eric A
SUMMARY  Chronic tic disorders are neuropsychiatric conditions characterized by the presence of motor or phonic tics that can cause distress and impairment. Although tic symptoms have been historically managed with psychotropic medications, behavior therapy presents an efficacious treatment option that is unaccompanied by concerns of medication management (e.g., side effects, drug–drug interactions and medication adherence). Previous case reports and randomized controlled trials have emphasized behavioral treatments in youth and adults, with minimal attention directed toward geriatric patient populations. We present the successful treatment of a 75-year-old woman with chronic motor tic disorder and describe how a manualized behavior therapy (Comprehensive Behavioral Intervention for Tics) was tailored to address the chronic symptom presentation relevant to geriatric patients with tics.